Predicting Romantic Interest and Decisions in the Very Early Stages of Mate Selection: Standards, Accuracy, and Sex Differences - FLETCHER, Garth J. O. (Institutional Knowledge at Singapore Management University, 2014)
In the current study, opposite-sex strangers had 10-min conversations with a possible further date in mind. Based on judgments from partners and observers, three main findings were produced. First, judgments of attractiveness/vitality perceptions (compared with warmth/trustworthiness and status/resources) were the most accurate and were predominant in influencing romantic interest and decisions about further contact. Second, women were more cautious and choosy than men—women underestimated their partner’s romantic interest, whereas men exaggerated it, and women were less likely to want further contact. Third, a mediational model found that women (compared with men) were less likely to want further contact because they perceived their partners as possessing less attractiveness/vitality and as falling shorter of their minimum standards of attractiveness/vitality, thus generating lower romantic interest. These novel results are discussed in terms of the mixed findings from prior research, evolutionary psychology, and the functionality of lay psychology in early mate-selection contexts.